1998
DOI: 10.1073/pnas.95.8.4386
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-X L interacts with Apaf-1 and inhibits Apaf-1-dependent caspase-9 activation

Abstract: Recent studies indicate that Caenorhabditis elegans CED-4 interacts with and promotes the activation of the death protease CED-3, and that this activation is inhibited by CED-9. Here we show that a mammalian homolog of CED-4, Apaf-1, can associate with several death proteases, including caspase-4, caspase-8, caspase-9, and nematode CED-3 in mammalian cells. The interaction with caspase-9 was mediated by the N-terminal CED-4-like domain of Apaf-1. Expression of Apaf-1 enhanced the killing activity of caspase-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
317
3
7

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(344 citation statements)
references
References 37 publications
11
317
3
7
Order By: Relevance
“…However, there is no obvious molecular mechanism linking anti-apoptotic Bcl-2 family members with the classical type 1 CD95/ FADD/caspase-8 pathway. Although it has been suggested that Bcl-2 and Bcl-X L directly (Boise and Thompson, 1997) or indirectly (Chinnaiyan et al, 1997;Han et al, 1997;Ng et al, 1997;Hu et al, 1998) bind caspase-8 and so modulate its activation (Medema et al, 1998), a recent report indicates that, in a system in which Bcl-X L e ectively suppresses CD95-induced apoptosis, Bcl-X L neither interacts with caspase-8 nor inhibits its recruitment or activation (Medema et al, 1998). This ®nding seems to leave little room for a role for Bad as an intermediary modulating activation of caspase-8 by FADD.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no obvious molecular mechanism linking anti-apoptotic Bcl-2 family members with the classical type 1 CD95/ FADD/caspase-8 pathway. Although it has been suggested that Bcl-2 and Bcl-X L directly (Boise and Thompson, 1997) or indirectly (Chinnaiyan et al, 1997;Han et al, 1997;Ng et al, 1997;Hu et al, 1998) bind caspase-8 and so modulate its activation (Medema et al, 1998), a recent report indicates that, in a system in which Bcl-X L e ectively suppresses CD95-induced apoptosis, Bcl-X L neither interacts with caspase-8 nor inhibits its recruitment or activation (Medema et al, 1998). This ®nding seems to leave little room for a role for Bad as an intermediary modulating activation of caspase-8 by FADD.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] As noted, CED-4 lacks the WD-domain repeats present in APAF-1 that are necessary for cytochrome c binding, and the release of CED-4 from sequestration by CED-9 appears to be sufficient to cause formation of the nematode apoptosome. Furthermore, despite early reports to the contrary 20,21 it is now accepted that mammalian Bcl-2 homologs do not functionally interact with APAF-1. [22][23][24] Given these significant differences, it is intriguing that the antiapoptotic functions of both Bcl-2 and CED-9 involve the mitochondria.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 99%
“…As mentioned before, in C. elegans CED-9 directly interacts with CED-4 preventing it from activating caspase CED-3. In mammalian cells, Bcl-x L has been reported to interact with the mammalian CED-4 homolog Apaf-1 and by that mechanism might prevent Apaf-1 from activating downstream caspases (Hu et al, 1998).…”
Section: Caspasesmentioning
confidence: 99%